Cell wall degrading enzyme induced rice innate immune responses are suppressed by the type 3 secretion system effectors XopN, XopQ, XopX and XopZ of Xanthomonas oryzae pv. oryzae. - Dipanwita Sinha; Mahesh Kumar Gupta; Hitendra Kumar Patel; Ashish Ranjan; Ramesh V Sonti (PLoS ONE, 2013)
Innate immune responses are induced in plants and animals through perception of Damage Associated Molecular Patterns. These immune responses are suppressed by pathogens during infection. A number of studies have focussed on identifying functions of plant pathogenic bacteria that are involved in suppression of Pathogen Associated Molecular Pattern induced immune responses. In comparison, there is very little information on functions used by plant pathogens to suppress Damage Associated Molecular Pattern induced immune responses. Xanthomonasoryzae pv. oryzae, a gram negative bacterial pathogen of rice, secretes hydrolytic enzymes such as LipA (Lipase/Esterase) that damage rice cell walls and induce innate immune responses. Here, we show that Agrobacterium mediated transient transfer of the gene for XopN, a X. oryzae pv. oryzae type 3 secretion (T3S) system effector, results in suppression of rice innate immune responses induced by LipA. A xopN (-) mutant of X. oryzae pv. oryzae retains the ability to suppress these innate immune responses indicating the presence of other functionally redundant proteins. In transient transfer assays, we have assessed the ability of 15 other X. oryzae pv. oryzae T3S secreted effectors to suppress rice innate immune responses. Amongst these proteins, XopQ, XopX and XopZ are suppressors of LipA induced innate immune responses. A mutation in any one of the xopN, xopQ, xopX or xopZ genes causes partial virulence deficiency while a xopN (-) xopX (-) double mutant exhibits a greater virulence deficiency. A xopN (-) xopQ (-) xopX (-) xopZ (-) quadruple mutant of X. oryzae pv. oryzae induces callose deposition, an innate immune response, similar to a X. oryzae pv. oryzae T3S(-) mutant in rice leaves. Overall, these results indicate that multiple T3S secreted proteins of X. oryzae pv. oryzae can suppress cell wall damage induced rice innate immune responses.